First Imitate, then Translate: Histories of the Introduction of Stream-of-Consciousness Fiction to China - Chan, Leo (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractIn China, stream-of-consciousness (SOC) fiction had for some time been thought of as untranslatable. By contrast, SOC imitations appeared in abundance through the twentieth century, attempted by several Chinese writers who consciously used the technique in their own novels, first in the thirties, then in the sixties, and finally in the eighties. It was not until the nineties, however, that the “difficult” novels by James Joyce and Virginia Woolf, among others, were translated. How can we understand the phenomenon of translations following imitations in the history of SOC fiction as introduced to China?